PERSEPSI MAHASISWA TENTANG FAKTOR-FAKTOR YANG MEMPENGARUHI PELANGGARAN HAK CIPTA DI UNIVERSITAS RIAU - Kusmitra Wijayanti; Gimin '; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by issues arising measure infraction copy right university studen, the particular infraction Constitution Copy Right No.28 year 2014 article 40 paragraph 1(a) Books, pamflet, countenance scientific rights publication, and all of them scientific work other. Infraction did university student as buy piracy book, reduplication book, copy a portion or plagiarism without permission and as product rights self. The now formulation problem research is the what is the factor-factor influence copy rights infraction be besed on university student in University of Riau?. The purpose of this research to the factor-factor influence copy rights infraction be based on the university student perception in University of Riau. Be based on the resultof this research that the percentage of the recapitulation of the answer to the questionnare respondent abouth the university student perception about the factor-factor influence copy rights infraction in University of Riau, 180 respondents 78,47% have the answer 7 factor influence copy rights infraction, wherease 21,53% answer No. From the 7 factor mentioned this factor influence copy right infraction dominant is: 1) the factor less illumination (91,11%), 2) the factor lees commed copy right other people (85,25%), 3) the factor social economi (84,16%), 4) the factor light in weight sanction law (81,11%). Wherease other the factor understanding about meaning and the fungtion copy right (63,16%), the factor social culter (66,39%) and the factor capability (78,06%) constitute factor less dominant.Keyword : factor-factor, infraction, copy rights